1987
DOI: 10.1021/bi00379a007
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of 3.alpha.,20.beta.-hydroxysteroid dehydrogenase with diethyl pyrocarbonate. Evidence for an essential, highly reactive, lysyl residue

Abstract: Diethyl pyrocarbonate inactivated the tetrameric 3 alpha,20 beta-hydroxysteroid dehydrogenase with second-order rate constants of 1.63 M-1 s-1 at pH 6 and 25 degrees C or 190 M-1 s-1 at pH 9.4 and 25 degrees C. The activity was slowly and partially restored by incubation with hydroxylamine (81% reactivation after 28 h with 0.1 M hydroxylamine, pH 9, 25 degrees C). NADH protected the enzyme against inactivation with a Kd (10 microM) very close to the Km (7 microM) for the coenzyme. The ultraviolet difference sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Presumably, the ~4C incorporations now first obtained corresponded to low amounts of Cys-containing contaminating protein chains, or to alkylation non-specific for Cys residues. Other reports mentioning Cys [16,17] also seem to lack specific proof. Combined, the different complications may indicate a reduced reliability at single positions.…”
Section: Directmentioning
confidence: 93%
See 1 more Smart Citation
“…Presumably, the ~4C incorporations now first obtained corresponded to low amounts of Cys-containing contaminating protein chains, or to alkylation non-specific for Cys residues. Other reports mentioning Cys [16,17] also seem to lack specific proof. Combined, the different complications may indicate a reduced reliability at single positions.…”
Section: Directmentioning
confidence: 93%
“…Finally, lack of Cys in the amino acid sequence (Fig. 2) was unexpected since a Cys residue has been postulated close to the steroid binding site [16,17] and a ~4C incorporation corresponding to 0.2-1 mol/mol was now initially found upon iodoacetate treatment, but could not be detected in the peptides, nor in the preparation analyzed (<0.3 mol/mol). Presumably, the ~4C incorporations now first obtained corresponded to low amounts of Cys-containing contaminating protein chains, or to alkylation non-specific for Cys residues.…”
Section: Directmentioning
confidence: 99%
“…However, the His residue claimed to be "affinity alkylated" by haloacetoxysteroids and chemically modified by diethyl pyrocarbonate (ref. 28 and references therein) is His-181, which is buried enough (Fig. 2C) to be inaccessible without some rearrangements of the active-site structure in this holo form.…”
Section: This Puts the Nad(h) Binding Region (3a-ab-(b--ac-(3c-mentioning
confidence: 96%
“…This indicates that hydroxylamine reverses the histidine modification by DEPC and strongly suggests that it reverses the lysine modification as well. DEPC modification of highly reactive lysine residues in proteins can be reversed by hydroxylamine as reported by Pasta et al (30), although an earlier report had concluded that reversibility was specific for histidine (16). Thus, reversal of DEPC modification of both histidine and lysine residues in the heparin-binding site of selenoprotein P seems likely because both histidine and lysine residues clearly contribute to the protein-heparin interaction.…”
Section: Discussionmentioning
confidence: 78%
“…Details of the experiment are given under "Experimental Procedures." hydroxylamine treatment can also reverse modification of lysine residues (30). This should be especially true in the case of highly reactive lysine residues.…”
Section: Table IV Mass Mapping Analysis Of Peptides Bound To Heparinmentioning
confidence: 99%